Green Education Crisis through Banking Business - Edwin Basmar; Nisa Novia Avien Christy (CV. Uruboros Publishing Group, 2025)
The research aims to detect, identify, and measure the green education crisis level in increasing economic stability and growth, through banking sector business activities as an intermediary function in financial circulation. The method used is quantitative with the Ed Waves Index Development Model, based on Bank Indonesia annual report data from 2000 to 2023 in time series using Eviews Version 9 software. The findings show that the high Non Performing Loan due to changes in macroeconomic behavior and increasing green education crisis, makes financial stability and economic growth difficult to achieve. The study results imply the importance of banking activities to be careful in providing credit to the industrial sector, whether oriented towards environmental sustainability or not, because the green education crisis risk has an indirect effect on financial stability and economic growth.